Research progress in preparation and application of g-C3N4-based heterogeneous photocatalyst for environmental pollutant removal - GE Yu-jie; WU Jiao; HE Zhi-qiang; WANG Guo-hua; LIU Jin-xiang (Cailiao gongcheng, 2021)
Graphite carbon nitride (g-C3N4) is a visible light responsive semiconductor material with the advantages of high stability, low cost, high adjustability of structure and property. With the continuous development of green and non-secondary pollution photocatalytic technology, g-C3N4has gradually become a research hotspot in the field of environment and energy science. Nevertheless, the bare g-C3N4 exhibits relatively low photocatalytic efficiency, which is due to the rapid recombination of photogenerated charge carriers and low visible light utilization efficiency. Among many modification methods, heterogeneous coupling is considered to be an effective method to improve the photocatalytic performance of g-C3N4. In recent years, with different inorganic semiconductors, precious metals, and carbon materials, heterogeneously coupled with g-C3N4, the researchers promoted the transfer efficiency of photoelectrons in the photocatalytic system, broadened the absorption range of visible light of g-C3N4-based photocatalysts, and enhanced the catalytic stability and structure regulation of g-C3N4. The catalytic mechanism of heterogeneous photocatalysts and construction of heterogeneous photocatalytic system based on g-C3N4 were summarized, the research progress of g-C3N4-based heterojunction in degradation of environmental pollutants was discussed. Finally, the prospect of designing excellent g-C3N4-based photocatalyst and their applications in photocatalytic degradation of dyes,organic pollutants and reduction of toxic heavy metals with excellent performance and its prospect in the field of environmental pollutant removal were prospected.